CONFISCATION OF PROPERTY AS A SANCTION IN LATVIA CRIMINAL LAW - Mežulis, Dainis (Administrative and Criminal Justice, 2019)
The purpose of the paper is to analyze confiscation of property as a criminal penalty in the criminal law of Latvia. According to the Section 42 of criminal law - confiscation of property is compulsory alienation of the property owned by a convicted person to the State ownership without compensation. Confiscation of property may be specified as an additional punishment to a deprivation of liberty or community service. Property owned by a convicted persons, which they have transferred to another natural or legal person, may also be confiscated. Confiscation of property may be specified only in the cases provided by Law. A court, in determining confiscation of property, shall specifically indicate which property is to be confiscated.At the same time - Chapter VIII.2 of criminal law has a very wide regulation of special property confiscation , that by law is not a criminal penalty, but a compulsory measure.The author believes that confiscation as a sanction must be excluded from law, as it is not in line with fundamental rights and is not efficient.Special confiscation and fine are more efficient and precisely regulated, which allow to respect human rights. Confiscation does not ensure balance between effectiveness and human rights with regards to general objectives of criminal justice system.